The investigation of complex influence of individual electricity quality parameters for the technical characteristics of asynchronous motor - Левченко, Сергій Андрійович; Коваленко, Віктор Леонідович; Мних, Антон Сергійович (Eastern-European Journal of Enterprise Technologies, 2012)
In the article the combined effect of asymmetry and nonsinusoidality voltages on the technical characteristics of an asynchronous motor are considered. The corresponding dependence for different load factors are given